Leadership, Cultural Development, and Competitiveness in Asia Pacific Multinational Companies - Jacobo Guevara, Breyci (2024)
Cultural development is a process that allows the emergence of novel elements and the gradual advancement of existing ones. The aim of the study was to analyze the factors involved in the cultural development of Asia Pacific multinational companies over the past twenty years. To achieve this, a systematic literature review was conducted, based on 38 scientific articles from Scopus. It was evident that having leadership aligned with the organization's objectives is essential, enabling employees to feel comfortable in their work. A predominant trend in research was identified towards qualitative approaches, as opposed to quantitative or mixed methods. Additionally, there was a predominant focus on evaluating multinational natured companies. The countries identified with greater relevance in this theme were the United States, Colombia, Mexico, the United Kingdom, and China. Finally, it is suggested that future research should focus on studies related to multinational innovative leadership.